Noninvasive diagnostic imaging of pelvic venous disorders - Szkodziak, Filip; Wozniak, Slawomir; Szkodziak, Piotr Robert; Pyra, Krzysztof; Paszkowski, Tomasz (Ultraschall in der Medizin - European Journal of Ultrasound, 2024)
It is estimated that chronic pelvic pain (CPP) may affect up to 24% of women. Unfortunately, very often, despite extensive diagnostics, the cause of CPP remains unknown. The pathophysiology of CPP could be explained to a large extent by the occurrence of pelvic venous disorders (PVD). Although pelvic venography is still considered the gold standard for the diagnosis of PVD, noninvasive diagnostic imaging techniques seem to be instrumental in the initial identification of patients with PVD. This literature review aimed to analyze and evaluate the usefulness of noninvasive diagnostic imaging techniques like transvaginal ultrasonography, transabdominal ultrasonography, magnetic resonance, and computed tomography in the diagnosis and identification of patients with PVD. Forty-one articles published between 1984 and 2023 were included in this literature review. Based on this literature review, we conclude that the clinical application of noninvasive diagnostic techniques in the diagnosis of PVD seems to be very promising. Future studies investigating the role of noninvasive diagnostic imaging techniques in the diagnosis of PVD are required.
Keywords: Pelvic Venous Disorders; Chronic Pelvic Pain; Ultrasonography; MRI; Noninvasive diagnostic imaging